Classical Dirichlet problem for the biharmonic equation in a semistrip with curvilinear end - Gomilko, A. M.; Trofimchuk, A. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
We prove the unique solvability of the Dirichlet problem in a classical formulation for the homogeneous biharmonic equation in a semistrip with curvilinear end.